The Effect of Rhizobium sp Inoculation and Nitrogen Fertilizer Application on the Growth, Yield, and Protein Content of Jack Bean (Canavalia Ensiformis L) Seeds - Dwiki Saputra; Budiman Sutisno; Ismail Saleh (Jurnal Agrosci, 2026)
Indonesia has a wealth of leguminous plants, one of which is jack bean (Canavalia ensiformis L). Jack bean has great potential as an alternative food source to replace soybeans and as an easily accessible source of protein at an affordable price. The objective of this study was to determine the effect of rhizobium inoculation and nitrogen fertilizer application on the growth, yield, and protein content of jack bean seeds. This study was conducted from June to November 2025 in Kaliaren Village, Kuningan, West Java, Indonesia. The study employed a Randomized Block Design (RBD) experimental method, consisting of 6 treatment combinations of nitrogen fertilizer dosage and rhizobium inoculation, repeated 4 times. Observation parameters included plant height, stem diameter, number of branches, RGR, NAR, weight of root nodules and weight of active root nodules (growth), number of pods, pod weight, dry seed weight (yield), and seed protein content. The results showed that there was no significant difference between treatments in terms of the protein content of jack beans, but the treatment of 200 kg N/ha and 0 g Rhizobium sp/kg seeds. had a significant effect on the growth and yield of jack beans.